2015
DOI: 10.3126/jpahs.v1i1.13024
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perception and Preference of Problem Based Learning During Introductory Course of a Nepalese Medical School

Abstract: Introductions: Problem based learning is considered superior to the conventional didactic teaching for contextual learning, long term retention of knowledge, development of generic skill and attitudes. This study looked in to the students’ perception and preference of problem bases learning in a sixmonth introductory course in the beginning of undergraduate medical school program. Methods: A 20-item questionnaire with four-point rating scale (1-strongly disagree, 2-Disagree, 3-Agree and 4-Strongly agree) was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 10 publications
1
12
0
1
Order By: Relevance
“…9 This suggested that at least 50 MCQs were required to achieve the minimum accepted internal consistency reliability of 0.70 even for self-assessment test with valid responses from 45 students or more in each organ-system blocks of PAHS-SOM. 2 Most of the students also advised to increase selfassessment MCQs and PBQs numbers and suggested to match the questions with that of the continuous endblock assessments as they found "more memory level MCQs in the self-assessment than in the end-block assessment". Based on this feedback, examination section was able to share 50 self-assessment MCQs and three self-assessment SISAQs for subsequent organsystem blocks with timely assistance from all the faculty involved in the integrated basic sciences program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 This suggested that at least 50 MCQs were required to achieve the minimum accepted internal consistency reliability of 0.70 even for self-assessment test with valid responses from 45 students or more in each organ-system blocks of PAHS-SOM. 2 Most of the students also advised to increase selfassessment MCQs and PBQs numbers and suggested to match the questions with that of the continuous endblock assessments as they found "more memory level MCQs in the self-assessment than in the end-block assessment". Based on this feedback, examination section was able to share 50 self-assessment MCQs and three self-assessment SISAQs for subsequent organsystem blocks with timely assistance from all the faculty involved in the integrated basic sciences program.…”
Section: Discussionmentioning
confidence: 99%
“…Self-directed learning is the main teaching/learning strategy of undergraduate medical education program at School of Medicine, Patan Academy of Health Sciences (PAHS-SOM) as its courses heavily use Problem Based Learning (PBL). 2 Thus, self-assessment of knowledge is also an integral part of student assessment system to help the students to appraise depth and breadth of knowledge a priori. Consequently, Multiple Choice Questions (MCQs) and Problem Based Questions (PBQ) are provided to them so that they can self-evaluate their knowledge during the organ-system blocks of the hybrid PBL program.…”
Section: Introductionsmentioning
confidence: 99%
“…Selanjutnya, Birgili (2015) juga menyatakan bahwa strategi PBL ini merupakan strategi yang memunculkan ide kreatif dan melatihkan kreativitas pebelajar. Dalam strategi PBL, bagian penting dari proses belajar adalah mengidentifikasi masalah (Bygholm & Buus, 2009;Ghimire & Bhandary, 2014 Munandar (2009), terdiri atas: 1) memiliki rasaingin tahu; 2) selalu merasakan tantangan; 3) keberanian mengambil risiko; 4) memiliki daya imajinasi dan respons mereka pada saat mengikuti diklat.…”
Section: Pendahuluanunclassified
“…At the Patan Academy of Health Sciences (PAHS), PBL is a major learning method. Students' perception regarding PBL during the introductory/foundation six month course at PAHS was studied [16]. Students showed a positive reaction toward PBL and agreed that it fostered generic skills (communication, group work, critical thinking, reasoning, reflection and SDL).…”
Section: Pbl In Nepalmentioning
confidence: 99%